Tinjauan Viktimologi Terhadap Anak dalam Tindak Pidana Penyalahgunaan Narkotika - Dianti, Anisa Rahma; Firmansyah, Hery (Universitas Ekasakti, 2023)
In facing the issue of drug abuse, Indonesia and ASEAN countries have committed to combating this global threat through various regional and international programs and cooperation. Despite Indonesia having relevant drug laws since 1997, the increasing complexity of drug abuse prompted a revision of these laws in 2009. The Narcotics Law defines narcotics as drugs that can be used for specific medical treatments, but when abused, can endanger society, especially the younger generation. Therefore, the law focuses on the abuse and trafficking of narcotics. However, addressing this issue is not easy as narcotics are an organized transnational crime. This article also discusses various terms related to drug use, including addicts, abusers, victims of drug abuse, and former addicts. The articles in the Narcotics Law also state sanctions for drug abusers, with an emphasis on medical and social rehabilitation. The importance of protecting children from drug abuse is also emphasized, with an explanation of the categories of children applicable in Indonesia. Children involved in drug abuse should receive legal protection in accordance with child protection laws. Furthermore, this article also discusses diversion as a restorative justice approach used in handling cases of drug abuse by children.